Limbic Encephalitis When the Immune Response Is the Hidden Problem - Amaral, M (2021)
Limbic Encephalitis (LE) defined as a rare and frequently underrecognized immunomediated syndrome, presents with a constellation of unspecific behavioral and neuropsychiatric symptoms, developing over weeks to months. Personality disturbance, complex partial mesotemporal seizures and a subacute severe impairment of short-term memory are the cardinal symptoms, reflecting the involvement of the grand lobe limbique. The etiology is still poorly understood. Until recently, paraneoplastic etiology was thought to be the most common cause of LE, often preceding the malignancy identification (60%–75%). In the last decade other associations have been considered, namely infectious or autoimmune diseases. It appears that non-paraneoplastic LE (unassociated with onconeural antibodies) is at least 5 times more frequent than the one where paraneoplastic antibodies are detected, even excluding the cases of paraneoplastic LE that are antibody-negative (40%). To date, co-occurrence of two possible etiologies of this rare syndrome, in the same patient, has never been reported.